Dorsal root ganglion stimulation device explantation: A multicenter pooled data analysis. Issue 5 (6th May 2022) - Chapman, Kenneth B.; Yang, Ajax; Mogilner, Alon Y.; Mandelberg, Nataniel; Patel, Kiran V.; Lubenow, Timothy; Deer, Timothy; Kallewaard, Jan Willem; van Helmond, Noud
Abstract: Introduction: Dorsal root ganglion stimulation (DRG‐S) is a relatively new neuromodulation modality. Therefore, data on long‐term device explantation rates is limited. This investigation aimed to assess DRG‐S device explantation rates at long‐term follow‐up. Methods: We retrospectively reviewed individuals implanted with DRG‐S in four pain centers from different continuous periods between April 2016 to September 2020. We recorded patient demographics, diagnoses, duration to explantation or last follow‐up, treatment complications, and failure etiologies. Results: A total of 249 patients with 756 leads and a mean 27‐month follow‐up were included. The mean age was 55 ± 15 years; 148 (63%) were female. Leading diagnoses were CRPS ( n  = 106, 43%), followed by FBSS ( n  = 64, 26%), and non‐surgical low back pain ( n  = 23, 9%). The explantation rate was ~2% per year ( n  = 10 total). At explantation, the average time from implantation was 13 ± 10 months. Six patients were explanted for inadequate pain relief. Two patients were explanted due to device‐related complications. One patient was explanted secondary to infection and subsequently reimplanted. Five explanted patients experienced a therapy‐related complication before eventual explantation: one transient post‐procedural neuritis and pocket site pain, one lead fracture, two lead migrations, and one experienced a fracture, a migration, and pocket site pain. Discussion: This large retrospective study of DRG‐S revealed a low therapy‐termination rate. The rate of infection leading to explantation was objectively very low at 0.4%. The leading cause of explantation was inadequate pain relief. Explanted patients often had a therapy‐related complication. Therefore, minimizing adverse treatment events may reduce ultimate explantation rates.